Bringing 19th Century Documents into the 21st Century via Social Network Analysis - Kim, Henry (Journal for the sociological integration of religion and society, 2014)
The social networks of U.S. Ministers in Korea from 1883 to 1905 were explored, and NodeXL was used to analyze official despatches. The findings evince a particular social structure that facilitated the burgeoning of Protestant missions, expansionism, and U.S. diplomacy in Korea at the turn of the 20th century. Though the author is aware of Horace N. Allen, the first American Protestant missionary to Korea as well as subsequent missionaries' impact on Korean Protestantism, the social network analysis in this paper was delimited by using historical documents from the three volumes of Korean-American Relations.